Pengaruh Produksi Bioetanol Melalui Fermentasi Oleh Ampas Tebu Dengan Variasi Penambahan Ragi Terhadap Nilai Kalor Dan Kadar Bioetanol - A.Wahid Al Farisi; Asroful Abidin; Mokh. Hairul Bahri (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The increasing energy demand and depleting fossil fuel reserves drive the development of eco-friendly alternative energy sources, such as bioethanol. Sugarcane bagasse, an agro-industrial waste with high lignocellulosic content, holds great potential for processing into bioethanol feedstock. Therefore, this study was conducted to examine the impact of varying dosages of Saccharomyces cerevisiae yeast on bioethanol production from sugarcane bagasse through fermentation, while also determining the most effective dosage. This research employed a laboratory experimental method utilizing three yeast dosage variations: 5 grams, 10 grams, and 15 grams. The fermentation process was carried out for 10 days, followed by four stages of distillation. The evaluation focused on four main parameters: moisture content, yield, bioethanol concentration, and calorific value. Based on the experimental results, oven-drying effectively reduced the moisture content of the sugarcane bagasse from 72% to 28%. Furthermore, it was found that an increase in yeast quantity was directly proportional to the concentration of the resulting bioethanol. The optimum result was achieved using 15 grams of yeast, which yielded a bioethanol concentration of up to 94% after the fourth distillation and recorded the highest calorific value at 2187.19 Cal/gram. In conclusion, increasing the yeast mass optimizes the fermentation process, thereby producing higher bioethanol concentrations and calorific values. This confirms that sugarcane bagasse holds great promise as a sustainable and eco-friendly feedstock for bioethanol production